PROFIL PERKEMBANGAN MOTORIK KASAR DALAM KEGIATAN LARI ESTAFET PADA ANAK KELOMPOK B RA HABIBI SINGOSARI-MALANG - Arun Dina Rahmawati; Ika Ratih Sulistiani; Yorita Febry Lismanda (UNISMA, 2019)
Relay activity in children is a gross motor development. This research is descriptive quantitative or quantitative description research, the data analysis technique uses descriptive with percent. This research was conducted at RA HABIBIE Singosari-Malang, this study was for group B children aged 5-6 years with a total of 20 children. In accordance with the results of this study concluded that the majority of children get four stars with several indicators, namely: 1) Children are able to run fast by carrying objects, without falling for 15 seconds; 2) Children are able to rotate and swing their arms 180º independently and quickly; 3) Children are able to receive objects precisely and quickly.